Development, Validation and Pharmacokinetic Application of a Simple and Robust RP-HPLC Method for Quantitation of Raloxifene in Rat Plasma - Mahmood, Syed; Sengupta, Pinaki; Mandal, Uttam K.; Chatterjee, Bappaditya; Taher, Muhammad (College of Pharmacists of Buenos Aires Province, Argentina, 2017)
SUMMARY. A simple and sensitive HPLC method has been developed and validated for the quantification of raloxifene in rat plasma. Liquid- liquid extraction procedure was employed for extracting raloxifene from rat plasma sample. Separation of raloxifene was achieved through a RP- C18 column with a mobile phase consisted of phosphate buffer and acetonitrile (66:34 %, v/v). The method was validated for specificity, selectivity, sensitivity, linearity, accuracy, precision, recovery and stability parameters. A linear response (R2 value 0.9991) was found over the calibration range of 50 to 500 ng/mL. The accuracy for intra and inter day run varied between 86.73 to 102.30 % and 91.11 to 95.56%, respectively. The corresponding precision (% CV) were within 0.82 to 9.43% and 6.23 to 8.33%. The method was also found to be specific and stable. The applicability of the method was established through a single dose oral pharmacokinetic study of raloxifene in rat.